High-temperature corrosion behavior of TP91, C22 alloy and C22 based on laser coatings in simulated reducing corrosion environment - Congcong Liu; Zongde Liu; Yuan Gao; Xinyu Wang; Chao Zheng (Materials Research Express, 2022)
To explore corrosion characteristics of TP91, C22 alloy and C22 laser coatings in reducing environment caused by low-nitrogen combustion at 500 °C–600 °C, a synthetic corrosive medium containing 0.2 vol% H _2 S-0.1 vol% O _2 –N _2 were selected. Results showed that the order of corrosion resistance is: C22 laser coatings>C22 alloy>TP91. 550 °C was the limit corrosion temperature for C22 alloy and C22 laser coatings. The reason for the strong corrosion resistance of C22 alloy and C22 laser coatings is that a dense layer of Cr-rich corrosion products due to the is produced in the inner layer, thus protecting the matrix from direct corrosion by corrosive gas. Finer grains before corrosion tests and the formation of dense Cr _2 O _3 inner layers in much speedier process were the main reasons for the best corrosion resistance of C22 laser coatings.